Classification of Environmental and Clinical Acinetobacter species Based on Some Antibiotics and Heavy Metals Resistant Genes (Medical Forum Monthly, 2026)
Objective: To evaluate cadmium resistance and genetic diversity in Acinetobacter isolates from clinical and environmental sources within hospitals.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the multiple hospitals in Baghdad City, Iraqi from 1st November 2024 to 31st March 2025.Methods: Sixty Acinetobacter species isolates were collected; 44 A. baumannii isolates (41 clinical, 3 environmental) and 16 Acinetobacter complex isolates (13 clinical, 3 environmental). The isolates were identified using the VITEK-2 system, and the diagnosis was confirmed using polymerase chain reaction for the blaOXA-51 gene. 22 representative isolates were selected for further analysis. Cadmium resistance tests were performed using the minimum inhibitory concentration method, and the czcB gene was detected using polymerase chain reaction. Genetic diversity was analyzed using enterobacterial repetitive intergenic consensus-polymerase chain reaction and biotyping tools.Result: All 22 isolates showed resistance to low cadmium concentrations (0.25mg/L, 0.125mg/L, and 0.0625 mg/L). The czcB gene was detected in 7 isolates (4 from A. baumannii and 3 from A. complex). Enterobacterial repetitive intergenic consensus-polymerase chain reaction demonstrated significant genetic diversity among the isolates. Cluster diagrams, heatmaps, and association matrices highlighted the phylogenetic relationships and unique characteristics of some isolates.Conclusion: Acinetobacter isolates showed significant resistance to cadmium, partly attributable to the presence of the czcB gene. Enterobacterial repetitive intergenic consensus-polymerase chain reaction has proven effective in elucidating genetic diversity and tracking potential sources of infection.